Surface contamination rates at different spatial scales in the Columbus module (ISS) during the MATISS campaigns - Lemelle, Laurence; Mottin, Eléonore; Le Tourneau, Denis; Rouquette, Sébastien; Campagnolo, Lucie; Thévenot, Cécile; Maillet, Alain; Barde, Sébastien; Garre, Emmanuel; Teisseire, Jérémie; Fontelaye, Caroline; Jousseaume, Vincent; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Future long-duration human spaceflights require developments to limit biocontamination of surface habitats. The three MATISS (Microbial Aerosol Tethering on Innovative Surfaces in the International Space Station) campaigns exposed surface treatments over several months in the ISS. Eight sample holders designed to this end were mounted with lamella-bearing FDTS, SiOCH, and parylene hydrophobic coatings, at two different locations, for several months, during three distinct periods from 2016 to 2020. Tile scanning optical microscopy (×3 and ×30 magnification) detected several thousand particles, indicating a relatively clean environment (a few particles per mm 2 ). In previous studies, exposure rates were analyzed for all the coarse and fine particles detected on the largest total area of the integrated FDTS area exposed in the ISS (several cm 2 ). Here, the contamination rates observed for a smaller constant area unit (the 0.66 cm 2 window area of the holder) were statistically analyzed. Therefore, a statistical difference between RGSH and EDR rates distributions, and between FDTS and either SiOCH, and Parylene rates distribution were shown for the coarse particles but not for the fine particles rates. The contamination rates were found to be low, confirming the efficiency of the long-term air purification system. The rates tend to vary with the astronaut occupancy rates. Surfaces of spacecraft for long duration exploration left unmanned during dormancy periods can be considered as safe from biocontamination.